Establishment of a serodiagnosis system for the detection of Toxocara spp. and Ascaris suum infection in chickens. (April 2020) - Nguyen, Yen Thi Hoang; Hayata, Yayoi; Sonoda, Shino; Nonaka, Nariaki; Maruyama, Haruhiko; Yoshida, Ayako
Abstract: Chickens are considered to act as paratenic hosts for agents, Toxocara canis, T. cati and Ascaris suum ; which cause ascarid larva migrans syndrome (ascarid LMS) in humans. In addition, they are the definitive host for Ascaridia galli, considered not to be infective for humans. All ascarid parasites can have a high homology of antigenicity, leading to cross-reactivity in serodiagnostic assays. This study was conducted to establish a procedure for the serological detection of those roundworm infections in chickens. Twenty-five male Julia chickens were divided into five groups ( n  = 5); T. canis-, T. cati-, Ascaris suum- and Ascaridia galli- infected, and an uninfected control group. In Ascaris suum -soluble worm antigen preparation (As-SWAP) ELISA, all infected groups showed an elevation of anti-ascarid antibodies, indicating the usefulness of As-SWAP as a screening antigen for the detection of ascarid infections. For infecting species identification, T. canis -excretory/secretory (Tc-ES) and Ascaris suum -ES (As-ES) antigen ELISA were conducted by serial dilution sera. Toxocara spp.-infected sera showed stronger binding to Tc-ES than As-ES, while Ascaris suum and Ascaridia galli -infected sera bound to As-ES more strongly than Tc-ES. To discriminate between Ascaris suum and Ascaridia galli infection, sera were pre-incubated with Ascaridia galli -SWAP antigen and applied to Tc-ES and As-ES ELISAs. In this pre-adsorbed ES antigen ELISAs, only the Ascaris suum infected group showed positive binding to As-ES, resulting from the adsorption of cross-reactive antibodies in Ascaridia galli -infected sera. Finally, anti- Toxocara specific antibodies were confirmed by Tc-ES western blot (WB). Toxocara spp.-infected sera showed toxocariasis-specific band pattern in Tc-ES WB, while no specific band appeared on any strip incubated with Ascaris suum, Ascaridia galli -infected and uninfected sera. In conclusion, the serodiagnostic assays evaluated in this study are useful for the detection of ascarid infections in chickens. Graphical abstract: Unlabelled Image Highlights: Toxocara canis, T. cati and Ascaris suum are the common causative species of ascarid larva migrans syndrome in humans. Chickens are considered as the paratenic host of T. canis, T. cati and Ascaris suum . In As-SWAP ELISA, anti-ascarid antibodies were detected in experimentally infected chicken sera. Toxocara spp. infections were detectable by the combination of Tc- and As-ES ELISA and Tc-ES western blot. Ascaris suum infection could discriminate with Ascaridia galli infection by pre-adsorbed ES antigen ELISAs.